INSTITUTIONAL ENVIRONMENT: IS IT AN ENABLER OR A CONSTRAINT TO FEMALE ENTREPRENEURSHIP? - Raushan Lesbekkyzy Aman; Kuralay Orazgalievna Nurgaliyeva (Academic Journal of Physical and Chemical Sciences, 2019)
Institutional environment is one of the main factors that influence the creation and maintenance of self-employment, and hence the entrepreneurship. However, previous research demonstrates that sometimes institutional environment may serve as a barrier to the development of entrepreneurship. Therefore, based on previous studies, authors make an assumption that institutional environment has a dual role in female entrepreneurship’s development of either being an enabler or a barrier. The article analyzes eight female entrepreneurs and the role of institutional environment in their business in the context of an emerging market - Kazakhstan. Semi-structured interviews were used in order to identify the role of institutions in female entrepreneurship’s development in Kazakhstan. The findings illustrate that female entrepreneurs in emerging markets are mostly provided with informal support from family, friends, and network. However, none of the interviewed businesswomen were getting formal support from local institutions. The results also demonstrate a positive cognitive attitude of a society towards entrepreneurship in the country under consideration.